Comparison of degree-day distribution models for predicting emergence of the cabbage aphid on canola. (February 2016) - Nematollahi, Mohammad R.; Fathipour, Yaghoub; Talebi, Ali A.; Karimzadeh, Javad; Zalucki, Myron P.
Abstract: Cabbage aphid, Brevicoryne brassicae (L.), is a serious pest on canola, Brassica napus L. Estimation of required degree-days for 50% emergence of the population is of special interest for controlling this aphid. To precisely predict 50% emergence of aphid populations as a function of accumulated degree-days, eight distribution models were tested. Models were evaluated statistically and validated with a separate data set collected from three canola fields. Observed cumulative emergence of the aphid was well described by three models. The sigmoid model proposed by Brown and Mayer was recommended to describe 50% emergence of the cabbage aphid population, because the model is simple and the parameter b denotes the accumulated degree-days at 50% emergence. The selected model could be used to better time insecticide applications and to more efficiently forecast aphids in canola fields. Highlights: A model was developed to predict 50% emergence of the cabbage aphid population. The selected sigmoid model can be used to better timing of insecticide application. The sigmoid model can be used to better releasing of the aphid natural enemies. The sigmoid model would be appropriate for forecasting the aphids in canola fields.